Framework approach as a strategy for research and design of complex spatial information systems (Using the example of NGDI) - Dyshlyk, O.; Chabaniuk, V. (Land Management, Cadastre and Land Monitoring, 2025)
The so-called Framework approach to the research and design of complex spatial information systems (SpIS) is considered. An example of such a SpIS is the National Geospatial Data Infrastructure (NGDI) of Ukraine in the sense documented as of the end of 2024 in the Law of Ukraine and in the Terms of Reference for the geoportal. Due to the ambiguity of the term, it is advisable to consider the approach from three points of view (interpretations). In this paper, attention is paid to one of these three points of view - the approach as a strategy. This strategy, as well as the Framework approach itself, are called constructive, because they are based on the so-called Conceptual Framework and Solutions Framework (SoFr) of the SpIS. According to the authors, the proposed strategy will solve the most important problem of the NGDI today - the actual lack of a strategy. In addition, the Framework approach will help solve the three biggest problems of the NGDI today: product, process and expertise (quality control).In the domains of NGDI and NSII (National Spatial Information Infrastructure) and in their contexts, the most important are three points of view (interpretations) on the Framework approach: 1) as a specific constructive strategy for using geographic information systems and technologies (GIS&T) to manage the territory of Ukraine; 2) as a generalization of the methodology for dealing with SpIS such as NGDI and NSII; 3) as a γ-method, which is denoted by γSoFr, where γ means general, and which “works” at the level (stratum) of IGIM (Integrated Geospatial Information Framework) for Ukraine. The limitations of the article allow us to dwell in more detail only on the consideration of the first interpretation. The second and third interpretations are only formulated for general understanding and with the expectation of sufficiency for conscious planning of the NGDI project.One of the concretizations of the Framework approach is the so-called “AtlasSF Framework Approach”. It is a generalization of the AtlasSF method and tool (Atlas Solutions Framework), which were previously used to create (classical) Atlas systems (AtS). The AtlasSF Framework approach is a hierarchy of three homogeneous Solutions Framework (SoFr) methods. They are called General (γ), Conceptual (β) and Application (α) SoFr, respectively, and are combined into a hierarchical system (model) - Conceptual Framework of the subject X, where X, in addition to AtS, can take the values of NGDI or NSII.The Framework approach in the NGDI project is proposed to be used as follows. The first problem – the product – is solved by harmonizing the model of the existing NSII of Ukraine with the INSPIRE model. To make this proposal constructive, the concept of Atlas GIS (AGIS, AGIS-CH) and the currently known implementations of its parts, proven in solving Cultural Heritage problems, are recommended for describing the necessary systems.The second problem – process – is solved by using the AtlasSF Framework approach. The specifics are the application of the γ-, β-, and α- SoFr methods of this approach. The not yet created γSoFr method should be a meta-method of βSoFr, working at the level (stratum) to which the IGIF projection for Ukraine belongs. The IGIF projection includes the National Spatial Data Infrastructure (NSDI) and its subset NGDI, βSoFr is an update of the GeoSolutions Framework, and αSoFr is the current revision of AtlasSF1.0+.The third problem – expertise (quality control) of key solutions – is solved by using the V-model of development, in which validation and verification of solutions must be immediately consistent with the requirements and architecture. In addition, the use of architectural patterns (frameworks) is a “native” property of the pattern. Otherwise, the pattern cannot be a “typical solution to a typical problem”.Keywords: Atlas Geoinformation System (AGIS), AtlasSF Framework approach, NGDI, NSDI, NSpAI, NSII, IGIF, INSPIRE.
Keywords: Atlas Geoinformation System (AGIS); AtlasSF Framework approach; NGDI; NSDI; NSpAI; NSII; IGIF; INSPIRE